Study of Smoking Effect on Some Liver Functions, Blood Pressure and Some Haematological Parameters in Smokers in Al-Muthanna Province - Duaa Hamad Hamza1 , Wafaa Abdulmutalib Naji2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aims of this study was to investigate the changes that occurred on some liver functions and somehaematologicl parameters and blood pressure of smokers. The current study is carried out in in Al- Muthannaprovince.The study included 200 men, (100) smokers and (100) non smokers (control ).the smokers and nonsmokers divided to two group according to age. the ages were between (25-46)years.The results for liverfunction indicate a significant increase at(P<0.05)in Glutamate Oxaloacetae Transaminase(GOT),GlutamatePyruvate Transaminase(GPT) and Alkaline Phosphatase ( ALP) levels of smokers comparing with controlgroup in two age groups ,but non-significant differences at (P<0.05) in Serum Total Bilirubin (STB) ofsmokers comparing with control group, While the results for haematological parameters showed a significantincrease at(P<0.05) in white blood cells (WBC), red blood cells(RBC), hemoglobin(Hb) and Mean CellVolume(MCV)of smokers comparing with non-smokers in two age groups, but non-significant differencesat(P<0.05) in PLT of smokers comparing with non-smokers in two age groups. the results for blood pressureshowed a significant increase at(P<0.05) in in systolic and diastolic blood pressure in all age groups ofsmokers comparing with non-smokers.